Nitrogen addition enhances seed yield by improving soil enzyme activity and nutrients - Mi, Wenbo; Luo, Feng; Liu, Wenhui; Qin, Yan; Zhang, Yongchao; Liu, Kaiqiang; Li, Wen (PeerJ, 2024)
Nitrogen (N) addition is a simple and effective field management approach to enhancing plant productivity. Nonetheless, the regulatory mechanisms governing nitrogen concentrations and their effect on soil enzyme activity, nutrient levels, and seed yield in the Festuca kirilowii seed field have yet to be elucidated. Therefore, this study sought to investigate the effect of N fertilizer application on soil enzyme activities, soil nutrients, and seed yield of F. kirilowii Steud cv. Huanhu, the only domesticated variety in the Festuca genus of the Poaceae family, was investigated based on two-year field experiments in the Qinghai–Tibet Plateau (QTP). Results showed that N input significantly affected soil nutrients (potential of hydrogen, total nitrogen, organic matter, and total phosphorus). In addition, soil enzyme activities (urease, catalase, sucrase, and nitrate reductase) significantly increased in response to varying N concentrations, inducing changes in soil nutrient contents. Introducing N improved both seed yield and yield components (number of tillers and number of fertile tillers). These findings suggest that the introduction of different concentrations of N fertilizers can stimulate soil enzyme activity, thus hastening nutrient conversion and increasing seed yield. The exhaustive evaluation of the membership function showed that the optimal N fertilizer treatment was N4 (75 kg·hm−2) for both 2022 and 2023. This finding provides a practical recommendation for improving the seed production of F. kirilowii in QTP.
Keywords: Festuca kirilowii Steud cv. Huanhu; Nitrogen addition; Soil enzyme activity; Nutrient content; Seed yield; Qinghai-Tibet Plateau